Food web-mediated interaction between marine mammals and fisheries in the Norwegian and Barents seas. - Bas, Lucas Johannes (UiT Norges arktiske universitet, 2023)
Ecological systems, such as marine ecosystems, are complex adaptive systems in which large scale system properties (e.g., trophic structure, energy flux patterns, etc.) emerge from interactions between ecosystem components or species. This makes them difficult to understand, predict, and model. The Norwegian and Barents Seas support multiple commercial fisheries, including those for herring, cod, and mackerel. Fisheries extract around 2.61 million tonnes of fish annually and marine mammals consume 11.7 million tonnes of fish and zooplankton annually in the region. The gradual change from conventional fisheries management towards ecosystem-based fisheries management (EBFM) requires that interactions and trade-offs between exploitation and conservation of fish and marine mammals be considered. Such trade-offs occurs when there is direct or food-web mediated competition for resources between fisheries and marine mammals. Recent diet studies suggest that there is limited direct competition between marine mammals and fisheries. Food-web mediated interactions may occur when mammals consume the prey of commercial fish species, or when fisheries target the prey of marine mammals, but evidence for such interactions is still lacking. Using Chance and Necessity modelling (CaN) we reconstruct possible dynamics of 12 trophospecies in the Norwegian and Barents Sea ecosystems during the period 1988-2021. The reconstructed dynamics are consistent with multiple observations of biomass, diet, consumption, and life-history characteristics of the species groups. We use these reconstructions to establish the level of empirical support for food-web mediated interactions between marine mammals and fisheries. The results of the model analysis indicate that there is limited evidence to support direct competitive interactions between marine mammals and fisheries in the Norwegian Sea, and mixed evidence for such interactions in the Barents Sea. The results showed that most direct interactions between the two groups were bottom-up driven, ...